Search for R -parity violating supersymmetry with displaced vertices in proton-proton collisions at s =8 TeV - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2017)
Results are reported from a search for R-parity violating supersymmetry in proton-proton collision events collected by the CMS experiment at a center-of-mass energy of ffiffi s p ¼ 8 TeV. The data sample corresponds to an integrated luminosity of 17.6 fb−1. This search assumes a minimal flavor violating model in which the lightest supersymmetric particle is a long-lived neutralino or gluino, leading to a signal with jets emanating from displaced vertices. In a sample of events with two displaced vertices, no excess yield above the expectation from standard model processes is observed, and limits are placed on the pair production cross section as a function of mass and lifetime of the neutralino or gluino. At 95% confidence level, the analysis excludes cross sections above approximately 1 fb for neutralinos or gluinos with mass between 400 and 1500 GeV and mean proper decay length between 1 and 30 mm. Gluino masses are excluded below 1 and 1.3 TeV for mean proper decay lengths of 300 μm and 1 mm, respectively, and below 1.4 TeV for the range 2–30 mm. The results are also applicable to other models in which long-lived particles decay into multijet final states.